Palestinian Costume - Weir, Shelagh (British Museum Press; Publications, London, 1989)
History and description of native and traditional dresses and jewellery from Palestine. Funded by The Welfare Association for The Palestinian Cultural Center. Other contributions from: Mahmoud Abu Ghazaleh, Faten Abu Ghazaleh, Bashar Al Huneidi, Hilda Dabdoub, Ibrahim Dabdoub, Sami Khourshid, George Nasra, Nabil Qaddoumi, Abdul-Muhsen Qattan, Abdulaziz Shakhshir, Samer Younes.
CONTENTS: --1. Introduction- Historical background, The Study --2. Materials and Merchants- Local raw materials, Dyes, Palestinian textiles, Egyptian textiles, Syrian materials, European textiles, Asian textiles, Shopkeepers and merchants, Buying the trousseau --2. Men's costume- The shirt, Overcoats, The long-sleeved coat, Jackets and waistcoats, Pants, Belts and sashes, Footwear, Head wear --3. Women's Costume- Body garments, The trousseau and the wedding, Regional styles and changing fashion, Coats, Dresses, Undergarments, Girdles and belts, Jackets, Shoes --4. Women's Costume- Headwear and Jewellery, Veils and headbands, Headdresses, Jewellery --5. Changing Fashions in Beit Dajan- Social background, The bride's contribution in the trousseau: early 1920s, Changes in Beit Dajan-style dresses: 1920s-1930s, The headdress and jewellery, The Kisweh --6. Wedding Rituals in Beit Dajan- The events of the wedding, The negotiations (tulbeh), The betrothal (mlak), Buying the kisweh, The henna night, The wedding day, The first bridal procession, The bride's nqut ceremony, the 'going out to the well' (tal'at al-bir) -- Postscript -- Notes -- Arabic transcription of Songs
English
Keywords: GR420-426 Folklore- By Subject- Costume, jewellery; Native dresses; Traditional dresses; Palestine